RETRACTED: Nexus Between Financial Development, Renewable Energy Investment, and Sustainable Development: Role of Technical Innovations and Industrial Structure - Dong, Xing; Akhtar, Nadeem (Frontiers in Psychology, 2022)
Significant challenges confronting China include reducing carbon emissions, dealing with the resulting problems, and meeting various requirements for long-term economic growth. As a result, the shift in industrial structure best reflects how human society utilizes resources and impacts the environment. To meet China's 2050 net-zero emissions target, we look at how technological innovations, financial development, renewable energy investment, population age, and the economic complexity index all play a role in environmental sustainability in China. Analyzing short- and long-term relationships using ARDL bounds testing, we used historical data spanning 1990 to 2018. According to the study's findings, the cointegration between CO2 emissions and their underlying factors was found. The deterioration of the environment directly results from the financial development, increasing economic complexity, and population aging. Technical advancements, investments in renewable energy sources, and changes to the industrial structure all contribute to lower CO2 emissions. Granger causality results were also reliably obtained in this study. According to our findings in the fight against environmental problems, a key tool for meeting long-term sustainability goals is policy prescriptions that use technological innovations, renewable energy investment, and industrial structure.